Association between type-2 diabetes and Toxoplasma gondii seropositivity: a systematic review and meta-analysis - Catchpole, Ashley; Zabriskie, Brinley N; Embley, Bradley; Kharazi, Hannah; Clarke, Rachelle; Templeton, Grace; Hunt, Christopher; Gale, Shawn D; Hedges, Dawson W (Folia parasitologica, 2025)
A metabolic disease resulting in elevated blood glucose levels, type-2 diabetes affects approximately 462 million people globally. Although its prevalence appears to be increasing, type-2 diabetes has been associated with various potentially preventable risk factors, including infectious diseases. The protozoal infection with Toxoplasma gondii (Nicolle et Manceaux, 1908) has been associated with type-2 diabetes in two previous meta-analyses. Since the publication of the last meta-analysis supporting an association between type-2 diabetes and T. gondii, several new primary studies have investigated this association. In this meta-analysis, we sought to further characterise the association between type-2 diabetes and T. gondii. We identified primary studies using PubMed, Embase, Scopus and Web of Science. Twenty-five studies met our inclusion criteria for a total of 4,639 patients with type-2 diabetes and 3,492 controls. Eighteen primary studies found a positive association between type-2 diabetes and T. gondii, whereas seven did not. Using a frequentist random-effects meta-analysis model, we found an overall summary odds ratio of 2.77 (95-percent confidence interval: 2.03-3.76), suggesting that the odds people will have type-2 diabetes is 2.7 times higher for people seropositive for T. gondii. Future studies should investigate this association in additional geographical regions and explore whether this association is due to the immunosuppressive effects of type-2 diabetes or whether T. gondii directly or indirectly affects glucose metabolism, or both.
Keywords: diabetes mellitus 2. typu; rizikové faktory; insulin-resistant diabetes; protozoal infection; diabetes mellitus; Toxoplasma; Diabetes Mellitus, Type 2; lidé; toxoplazmóza; Toxoplasmosis; Risk Factors; metabolic disorder; Humans; toxoplasmosis